Intertextualidade, gênero e identidade : as representações da cortesã em Lucíola, Lúcia McCartney e Lúcia - Antunes, Gracinete Franco (2007)
The subject matter of this dissertation is the prostitute role in the brazilian literature, from the point of view of the novel Lucíola (1862) by José de Alencar. We entend to interconnect this novel, written in the second half of the nineteenth century, with two. other literary texts that are weaved in the XX th century. The first evidence of the José de Alencar`s novel influence occurs through the reading of the tale Lúcia McCartney (1967), by Rubem Fonseca, which reproduces the way of life in the 60s and reveals character Lúcia, in her dayly life of exploitation and marginalicity, very usual in big cities. The second evidence appears in the novel Lucia (1999), by Gustavo Bernardo, who, at the same time gives life to two Lúcias : one of them is an idealized woman and the other one having a distorted behavior. Gustavo Bernardo tries to establish patterns and values for the female sex and for the re-reading of the tradition, in a scope of the contemporary life. The studied authors deal with the topic of prostitution under the light of patriarchal conservativeness, that shows the intention to re-read the female condition, having as a proposal the inter-textual character of the novels, the matters of gender (passing between the concepts of House & Street) and the female cultural identity within the deeply social and structural changes of the habits in Brazil.